The R4 Rural Resilience Initiative: An Integrate Climate Risk Management Approach - Renart, Jordi (2019)
Jordi Renart Building Resilience through Financial Inclusion: A Review of Existing Evidence and Knowledge Gaps Co-Organized by IFPRI and Innovations for Poverty Action (IPA) MAY 9, 2019 - 12:15 PM TO 01:45 PM EDT